Implementasi Algoritma Apriori Untuk Prediksi Penjualan Produk Packaging Di Pt. Printec Perkasa Ii - Ermanto Ermanto; Herlen Tamba (Jurnal SIGMA, 2018)
Inventory management of goods stock is an important problem faced by companies, especially trading. To support the smooth running of trade which will ultimately affect the smooth fulfillment of consumer demand, management must always try to ensure the availability of stock of goods. However, inventory management that is less than optimal can lead to over-stock of goods in a company. Therefore, in the inventory management of inventory goods in warehouses, it is necessary to have an information system application for data entry and exit of goods and to make it easier to control the supply of goods carried out by warehouse staff. Warehouse staff section at PT. Mighty Printec II functions as a processor of data stock of goods relating to making reports of entry and exit of goods and stock of goods, the collection and writing of this Final Project uses observation techniques, interviews and uses the method of library research with secondary data as the source of the data. Things that become one of the obstacles in the implementation of work are still found errors in the processing of data out the entry of goods and stock of goods which will be used as material for making daily, weekly and monthly reports. By creating a stock information system in the warehouse of PT. Printec Perkasa II desktop-based it can help reduce errors in processing the data entry and exit of goods stock items that will be used as material for making reports